2014
DOI: 10.1002/mabi.201400362
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Nanodevices in Biomedical Applications

Abstract: In the last couple of decades several drug carriers have been tailored on the nanometric scale by taking advantage of new stimuli responsive materials. Thermoresponsive polymers in particular have been extensively employed as stimuli-responsive building blocks that in combination with other environmental-responsive materials allowed the birth of smarter systems that can respond to more than one stimulus. Examples that highlight the different polymers for thermally triggered drug delivery will be described. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 109 publications
(158 reference statements)
0
48
0
Order By: Relevance
“…2,3 A shared characteristic of commercialized nanomaterials for clinical use is that they are typically designed for only one specific application (either diagnosis or therapy), and a vast majority of them are only developed to look for an improvement in the drug dosage or pharmaceutical efficacy. 2,3 A shared characteristic of commercialized nanomaterials for clinical use is that they are typically designed for only one specific application (either diagnosis or therapy), and a vast majority of them are only developed to look for an improvement in the drug dosage or pharmaceutical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 A shared characteristic of commercialized nanomaterials for clinical use is that they are typically designed for only one specific application (either diagnosis or therapy), and a vast majority of them are only developed to look for an improvement in the drug dosage or pharmaceutical efficacy. 2,3 A shared characteristic of commercialized nanomaterials for clinical use is that they are typically designed for only one specific application (either diagnosis or therapy), and a vast majority of them are only developed to look for an improvement in the drug dosage or pharmaceutical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The observed size variation with temperature confirmed that the nanoparticles display thermosensitive behavior, provided by Pluronic‐F127. This temperature‐dependent feature should also help to validate these CLPMs as suitable candidates for responsive drug carriers …”
Section: Resultsmentioning
confidence: 99%
“…This temperature-dependent feature should also help to validate these CLPMs as suitable candidates for responsive drug carriers. [18]…”
Section: Preparation and Morphological Characterization Of Clpmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the combination of inorganic nanoparticles with interesting physical properties can be incorporated into the nanogel network. For example, magnetic particles can be combined into a nanogel matrix forming magnetic nanogels (MNG) [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%